Penerapan Model Discovery Learning Berbantuan Quizizz untuk Meningkatkan Hasil Belajar Matematika Peserta Didik - Nusywari, Widya; Rabbani, Aftina; Suprihatin, Titin; Hauli, Zulfiana (Griya Journal of Mathematics Education and Application, 2024)
This study aims to improve students' mathematics learning outcomes by implementing the discovery learning model assisted by quizizz. The subjects of the study were 30 eighth-grade students from SMP Negeri 1 Labuhan Haji, Lombok Timur. The research used a classroom action research (CAR) method conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. The results showed a significant improvement in learning outcomes from the pre-cycle to cycle I and cycle II. In the pre-cycle, only 23.33% of students achieved mastery, with an average score of 45.31. After the implementation of the discovery learning model assisted by Quizizz in cycle I, the mastery percentage increased to 56.70%, and in cycle II, it reached 90.00% with an average score of 86.21. Based on these results, it can be concluded that the implementation of the discovery learning model assisted by quizizz is effective in improving students' mathematics learning outcomes.